Storytelling Methods by Nurses on Children's Anxiety Levels During Hospitalization - Indrayadi Indrayadi; Wahyuni Anwar; Kasmiati Kasmiati; Rachmat Ramli (International Journal of Health Sciences, 2026)
ABSTRACT Hospitalization in children often causes anxiety caused by the new environment, medical procedures, and separation from family. High anxiety can impact the child's psychological condition and hinder the healing process. One non-pharmacological intervention that can be carried out by nurses to reduce children's anxiety is the storytelling method. This study aims to determine the effect of the storytelling method by nurses on children's anxiety levels during hospitalization. The study used a quasi-experimental design with a pretest - posttest approach. The study sample consisted of 40 children undergoing treatment in the pediatric inpatient ward. Measurement of anxiety levels was carried out using a child anxiety scale before and after the storytelling intervention. Data analysis used a paired t- test. The results showed a significant decrease in children's anxiety levels after the storytelling intervention (p < 0.001). It was concluded that the storytelling method is effective in reducing children's anxiety levels during hospitalization. Keywords: Storytelling, Child Anxiety, Hospitalization, Pediatric Nursing